Parliament, People or Technocrats? Explaining Mass Public Preferences on Delegation of Policymaking Authority. (March 2022) - Beiser-McGrath, Liam F.; Huber, Robert A.; Bernauer, Thomas; Koubi, Vally
While delegation of policymaking authority from citizens to parliament is the most defining characteristic of representative democracy, public demand for delegating such authority away from legislature/government to technocrats or back to citizens appears to have increased. Drawing on spatial models of voting, we argue that the distance between individuals' ideal policy points, the status quo, experts' policy positions and aggregated societal policy preferences can help explain whether individuals prefer to delegate decision-making power away from parliament and, if so, to whom. The effects of individual's preference distance from these ideal points are likely to be stronger the more salient the policy issue is for the respective individual. We test this argument using survey experiments in Germany, Switzerland and the United Kingdom. The analysis provides evidence for the empirical implications of our theoretical arguments. The research presented here contributes to better understanding variation in citizens' support for representative democracy and preferences for delegating policymaking authority away from parliament.